Learning to Manage COVID-19-induced Respiratory Distress in the Immersive Virtual Reality Simulation: A Pre-Experimental Study - Yurkiv, Halyna; Catallo, Cristina; Newman, Kristine (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2025)
Introduction: Undergraduate nursing students have limited theoretical knowledge of and practical learning opportunities to manage COVID-19 respiratory distress. Immersive virtual reality simulations in nursing represent a new area of educational interest that has been understudied in Canada. Objective: This study aimed to measure the potential impact of immersive virtual reality simulation on content knowledge in respiratory distress induced by COVID-19, as well as perceived learning and perceived confidence in managing this condition among third- and fourth-year undergraduate nursing students. Methods: A pre-experimental design with a one-group pretest-post-test was employed. Nursing students (n = 30) were recruited through convenience sampling to participate in a single immersive virtual reality simulation session. Data were collected using the Respiratory Distress Management Knowledge Test, the Simulation Effectiveness Tool-Modified (subscales: Learning and Confidence), and an open-ended question. Results: The results showed an increase in knowledge (p=0.01). Participants reported a high perception of learning and confidence, and shared that this simulation helped them identify areas for improvement and strengthened their existing skills. Discussion and Conclusion: These results suggest that this immersive virtual reality simulation has the potential to enhance students’ knowledge about respiratory distress. Subjective evaluations highlight its educational potential. Further studies could explore simulation’s impact on nursing students and professionals by integrating a control group and other validated measures.